2017
DOI: 10.1007/s00270-017-1802-2
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Popliteal Sciatic Block Provides Adequate Analgesia During Urgent Endovascular Treatment of Critical Limb Ischemia with Resting Pain

Abstract: Level 4, case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Ideally, relief of pain is achieved by reperfusion of the limb in patients with CLI [1,2]. Pain control may be urgently needed in these patients until revascularisation can be provided [1][2][3]9,15,16]. In severe cases, the pain occurs only after a short period of supine rest, and it may become impossible for the patients to lie on their back for a long time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ideally, relief of pain is achieved by reperfusion of the limb in patients with CLI [1,2]. Pain control may be urgently needed in these patients until revascularisation can be provided [1][2][3]9,15,16]. In severe cases, the pain occurs only after a short period of supine rest, and it may become impossible for the patients to lie on their back for a long time.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients with CLI exhibit symptoms of anxiety and poor compliance with prolonged revascularisation procedures. Moreover, they may have abnormal behaviour involving hyperactive or hypoactive psychomotor activity, disturbances of attention, or disorientation [1][2][3]8,15,16]. Although they may need effective pain control with higher levels of opioid medications during these interventions, they have poor tolerance to strong opioids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing studies suggested that intravenous morphine 10 and ultrasound-guided peripheral nerve block provided satisfactory analgesia effect on patients with CLI. [11][12][13][14] However, the analgesia effect of intravenous morphine and ultrasound-guided regional block has not been compared before. Therefore, in this study, we plan to compare the perioperative analgesia effect of patient-controlled regional analgesia (PCRA) and patient-controlled intravenous analgesia (PCIA) for patients diagnosed with CLI.…”
Section: Open Accessmentioning
confidence: 99%